(untitled) (Conferencea, 2022)
Effect of cellulases and proteinases on carbohydrates and proteins of black cotton oil is studied. Processing of crude cotton oil neutral proteinase in combination with cellulolytic enzymes positively influences enzymatic processes and increases degree of hydrolysis of proteins and carbohydrates